Perbedaan Karakteristik Sebaran Spasial Hujan di Kabupaten Jember Menggunakan Metode Inverse Distance Weighted (IDW) dan Poligon Thiessen - Roni Bahtiar; Yagus Wijayanto; Subhan Arif Budiman; Tri Wahyu Saputra (Berkala Ilmiah Pertanian, 2022)
Rain is one of the elements that make up the climate. Rainfall in an area can be influenced by many factors. The rainfall data at a point in the rain station only represents the area at that point. Interpolation is done to present the rainfall data so that it can be easily understood. This study was conducted to determine the characteristics of the spatial distribution of rain in Jember Regency using the Thiessen Polygon and Inverse Distance Weigthed (IDW) methods and to determine the best method between the two. The data used in this study are the annual average rainfall data that has been obtained Perusahaan Daerah Perkebunan (PDP) Kahyangan Jember, Dinas PUPR Sumber Daya Air, and PTPN XII. Data processing is carried out using the ArcGIS program, and then a rainfall distribution map is made. The RMSE (Root Mean Square Error) calculation was carried out using the IDW method using 5 power levels, namely 0.5, 1, 2, 3, and 4. The results of calculations using the Thiessen polygon method produce a characteristic distribution of rainfall in which the rainfall decreases with the area moving south towards the coast. The Inverse Distance Weighted (IDW) method shows diversity with the lowest value being 94.71 mm and the highest being 406.92 mm per year. The power value 4 shows the RMSE calculation result of 0.00026 which is the lowest value.